Surgical strategy of empyema thoracis in children: open thoracotomy v/s video assisted thoracoscopy - Jadhav, Pranav; Raut, Sanjay; Kashyap, Manish Kumar; Bora, Riddhi Ajay (International Surgery Journal, 2018)
Background: Empyema is the suppuration within the pleural cavity, most commonly a complication of acute bacterial pneumonia. It is one of the most common diseases in children in India. Prognosis is excellent, provided appropriate treatment is administered early in the course of the disease. Methods: This study examines treatment of complex empyema thoracis between June 1, 2016, and April 30, 2018. Total number of patients were 30 cases in open thoracotomy and 30 in VATS in treatment of their disease. Effusion etiology was distributed as follows: infectious, neoplastic-associated, traumatic. Results: A total of 30 patients underwent VATS debridement and open thoracotomy for treatment of empyema thoracis. The median postoperative hospital stay was 10.31±3.751 days in case of VATS and 4.41±1.593 days in case of open thoracotomy. Median estimated blood loss in case of VATS was 78±15.634 ml and in case of open thoracotomy was 15.97±5.871 ml. Mean operative time was 82.86±17.293 minutes in case VATS and 77.59±13.38 minutes in case of open thoracotomy. Conclusions: VATS might be comparable or even better than open thoracotomy in terms of operative time, postoperative hospital stay, chest tube duration, prolonged air leak rate, morbidity and mortality. But referring to the relapse rate, there was no statistical significance.